2021
DOI: 10.1007/s10620-021-07160-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling of Colonoscopic Findings in a Fecal Immunochemical Test-Based Colorectal Cancer Screening Program

Abstract: Background The fecal immunochemical test (FIT) is the primary modality used by the Los Angeles County Department of Health Services (LADHS) for colorectal cancer (CRC) screening in average-risk patients. Some patients referred for FITpositive diagnostic colonoscopy have neither adenomas nor more advanced pathology. We aimed to identify predictors of false-positive FIT (FP-FIT) results in our largely disenfranchised, low socioeconomic status population. Methods We conducted a retrospective study of 596 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similarly, a retrospective study by Law et al 8 supported increased odds of a false-positive FIT given the presence of hemorrhoids on the basis of multiple logistic regression, although a history of hemorrhoid-associated bleeding was unknown. 8 Lack of firm awareness of hemorrhoid-associated bleeding may be more typical of the real-world, but this does not lend greater strength to study conclusions if known or measured.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, a retrospective study by Law et al 8 supported increased odds of a false-positive FIT given the presence of hemorrhoids on the basis of multiple logistic regression, although a history of hemorrhoid-associated bleeding was unknown. 8 Lack of firm awareness of hemorrhoid-associated bleeding may be more typical of the real-world, but this does not lend greater strength to study conclusions if known or measured.…”
Section: Discussionmentioning
confidence: 92%
“… 7 By contrast, a more recent study found that hemorrhoids were associated with higher odds of a false-positive FIT. 8 …”
mentioning
confidence: 99%
“…This study showed that hemorrhoids and female sex were linked with higher odds of FP-FIT and fewer advanced adenomas, whereas increasing age and body mass index were associated with lower odds of FP-FIT and more advanced adenomas. In FITpositive patients, the choice to perform a diagnostic colonoscopy may be influenced by the existence of the above-mentioned indicators [36]. Such FP-FIT results subject patients to unnecessary colonoscopies, which raises the burden and cost of healthcare, subject patients to unnecessary interventions, decrease adherence to treatment with yearly FIT testing and can cause psychological distress for up to six weeks after a typical colonoscopy [35][36][37].…”
Section: Fecal Immunochemical Testmentioning
confidence: 99%
“…In FITpositive patients, the choice to perform a diagnostic colonoscopy may be influenced by the existence of the above-mentioned indicators [36]. Such FP-FIT results subject patients to unnecessary colonoscopies, which raises the burden and cost of healthcare, subject patients to unnecessary interventions, decrease adherence to treatment with yearly FIT testing and can cause psychological distress for up to six weeks after a typical colonoscopy [35][36][37].…”
Section: Fecal Immunochemical Testmentioning
confidence: 99%
See 1 more Smart Citation